Escala de estresse percebido aplicada a estudantes universitárias: estudo de validação - Dias, Juliana Chioda Ribeiro [UNESP]; Silva, Wanderson Roberto [UNESP]; Maroco, João; Campos, Juliana Alvares Duarte Bonini [UNESP] (Leibniz Institute for Psychology (ZPID), 2015)
Aim: To present a Portuguese (post-orthographic agreement) version of Perceived Stress Scale (PSS) and estimate its validity and reliability in Brazilians female college students. Method: The face and content validity were estimated. Confirmatory factor analysis (n = 1081) was conducted and the goodness-of-fit indices used were the chi-square by degrees of freedom ratio (χ²/df), the Comparative Fit Index (CFI), the Normed Fit Index (NFI) and the Root Mean Square Error of Approximation (RMSEA). The stability of the best model for independent samples was verified by multigroup analysis and the invariance by difference of chi-squares (Δχ²) for factor weights (λ), covariance between factors (Cov), and residues (Res). The convergent validity was estimated by the Average Variance Extracted (AVE) and Composite Reliability (CR). The concurrent and divergent validity of PSS were estimated by Pearson’s correlation analysis (r) with the Weight Concerns Scale and the Maslach Burnout Inventory, respectively. The internal consistency was estimated by standardized Cronbach’s alpha coefficient (α). Results: The 10-item version (PSS-10) showed better fit to the sample (χ²/df = 10.69; CFI = .90; GFI = .93; RMSEA = .09). The convergent validity was below recommended (AVE = .34; CR = .84). The internal consistency (α = .83) was adequate. The structure was stable in the independent sub-samples. The concurrent and divergent validity were adequate. Conclusion: The PSS-10 presented adequate validity, reliability and stability in independent samples of university students.

Objetivo: Apresentar uma versão em português (pós-acordo ortográfico) da Escala de Estresse Percebido (PSS-14), e estimar sua validade e confiabilidade em universitárias brasileiras. Método: Realizaram-se validações de face e conteúdo. Realizou-se análise fatorial confirmatória (n = 1081) e utilizando-se como índices de ajustamento a razão qui-quadrado por graus de liberdade (χ²/gl), Comparative Fit Index (CFI), Normed of Fit Index (NFI) e o Root Mean Square Error of Approximation (RMSEA). Avaliou-se a estabilidade do melhor modelo em amostras independentes por análise multigrupos e a invariância pela diferença do qui-quadrado (Δχ²) para os pesos fatoriais (λ), Covariância entre fatores (Cov) e Resíduos (Res). Estimou-se a validade convergente pela Variância Extraída Média (VEM) e Confiabilidade Composta (CC). As validades concorrente e divergente da PSS foram estimadas por análise correlacional de Pearson (r) com a Weight Concerns Scale e o Inventário de Burnout de Maslach, respetivamente. A consistência interna foi estimada pelo Coeficiente alfa de Cronbach padronizado (α). Resultados: A versão de 10 itens (PSS-10) apresentou melhor ajustamento à amostra (χ²/gl = 10,69; CFI = 0,90; GFI = 0,93; RMSEA = 0,09). A validade convergente esteve abaixo do recomendado (VEM = 0,34; CC = 0,84). A consistência interna (α = 0,83) foi adequada. A estrutura foi estável nas subamostras independentes. As validades concorrente e divergente foram adequadas. Conclusão: A PSS-10 apresentou adequada validade, confiabilidade e estabilidade em amostras independentes de estudantes universitárias.
Perceived Stress Scale Applied to College Students: Validation Study
Keywords: Stress; Validation studies; Reliability; Psychometrics; College students; Young adults; Estresse; Estudos de validação; Confiabilidade; Psicometria; Estudantes universitárias; Adulto jovem